2012
DOI: 10.1111/j.1365-2818.2012.03617.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon microscopy: resolution, sensitivity and crosstalk

Abstract: SummaryThis paper develops the theoretical framework to understand the capability of the interferometric surface plasmon microscope to quantify sample properties in a confined region. We use rigorous diffraction theory to quantify the ability of the system to measure local properties and eliminate crosstalk from adjacent regions. We argue that the interferometric system in the defocused condition defines the measured point of excitation and reradiation of the surface plasmons; which greatly improves localisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
(22 reference statements)
0
31
1
Order By: Relevance
“…9, the longer the range of defocus used to calculate the wave vector of the SP, the more accurate the measurement, on the other hand, reducing the maximum defocus improves the lateral resolution. 5 We used the artificial plasmon method to measure the local gradient over a narrow range of defocus corresponding to the flat region from 22400 to 22100 nm. By phase stepping the region with predominant p-polarization, we obtained curves for the variation of w(z) shown in Figure 6 for the five regions of the sample; we see that the R2 curve is approximately horizontal, whereas R0 and R1 have positive gradients and R3 and R4 have negative gradients as expected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…9, the longer the range of defocus used to calculate the wave vector of the SP, the more accurate the measurement, on the other hand, reducing the maximum defocus improves the lateral resolution. 5 We used the artificial plasmon method to measure the local gradient over a narrow range of defocus corresponding to the flat region from 22400 to 22100 nm. By phase stepping the region with predominant p-polarization, we obtained curves for the variation of w(z) shown in Figure 6 for the five regions of the sample; we see that the R2 curve is approximately horizontal, whereas R0 and R1 have positive gradients and R3 and R4 have negative gradients as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Extending the 'flat' artificial plasmon range will improve the signal to noise even more as demonstrated in Ref. 5 for the system with the normal reference beam. Approaches to extend the flat region are discussed below.…”
Section: Surface Plasmon Confocal Interferometrymentioning
confidence: 94%
See 2 more Smart Citations
“…In recent years there has been a growing interest in performing surface plasmon (SP) measurements within a microscopic environment [1][2][3][4][5][6]; this offers the possibility of obtaining localized high resolution measurements of local changes in refractive index as well as performing valuable imaging of cell attachment [7][8][9]. We have shown that the lateral resolution of SP microscopy is optimized with an interferometric arrangement and we have more recently demonstrated that similar performance can be achieved with a confocal microscope arrangement [5].…”
Section: Introductionmentioning
confidence: 89%